Exploring the Language Values and Local Wisdom in the Legend of Si Pahit Lidah for Culture-Based Student Learning - Eka Putri; Luciana Lidya Sari; Sri Wahyuni; Wasitoh Meirani (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This research focuses on the integration of language and local wisdom, particularly in the legend of Si Pahit Lidah, with learning activities in an academic environment, specifically for students of the Chemical Engineering Department. The goal is to create culture-based learning that can enrich students’ understanding not only in the scientific aspects of engineering, but also in the aspects of local values and language. In the context of learning in the Chemical Engineering Department, this approach can be a pedagogical innovation that integrates local cultural elements into general Indonesian language courses. Thus, the exploration of language values and local wisdom in the legend of Si Pahit Lidah not only plays a role in cultural preservation, but also contributes to a more contextual, humanistic, and culturally rooted learning approach, particularly in vocational higher education environments such as the Chemical Engineering Department. The method used in this research is a descriptive qualitative method. The data source for this research is the legend of Si Pahit Lidah, originating from South Sumatra. Data collection techniques used documentation and note-taking techniques to support this research. Data analysis techniques used categorization stages consisting of linguistic values and local wisdom values. Linguistic values consist of three values: (1) aesthetic value of language, (2) educational value, and (3) communicative value. Meanwhile, there are four local wisdom values: (1) social value, (2) moral value, (3) cultural value, and (4) spiritual value. These linguistic values and local wisdom can be used as inspirational and appreciative reading and learning materials for students in the Chemical Engineering Department as a form of cultural preservation.